(3oZQQ GdNUGFU GdhGVMI hoYQQ GdfbGFU GdaGVMIs - (3eMeO Hf EHQGgje Hf jMji Hf Ydj GdCfUGQj GdcJHj, LeGd GdOjf, GdeYQha H` GdhWhGW,J (B718 (3g` s
(3ChdgG (B:s
(3hHYO aEfj deG QCjJ JZGjQ eYGfj GdCNdGb, OGdkG Ydi JHGjf eHGfj GdCYQGb s
(3BNQgG (B:s
(3hPdc eG dG jLOhf Je GdLRA GdChd hjdjg GdLRA GdKGfj GdPj Chdg HGH GdSNGA s
(3HgG fXGe GdJYbjHIs
(3UaMI GdYfhGf ePgHIs
(3fSNI KGdKIhJJab aj ChdgG eY GdfSNI GdChdi HGNJdGa aj HYV GdCdaGX hJJab aj BNQgG eY GdfSNI GdKGfjIs
(3fSNI NRGFfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B297 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B222 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B143s
Keywords: (3GdCOHs